Effect of sorption on the active concentration of polymer support fluids. Issue 1 (9th March 2021) - Lam, C.; Jefferis, S. A.
Abstract : Solutions of partially hydrolysed polyacrylamides (PHPAs) are regularly used as excavation-support fluids for the construction of bored piles. Their use in grab-excavated diaphragm walls is also developing. However, it is known that PHPA molecules can sorb onto soils and so the concentration of active polymer in a support fluid will reduce with use. To assess the effect of polymer sorption on clays, a series of batch sorption experiments has been conducted using a high-molecular-weight PHPA and three clays: kaolin, London clay and bentonite (smectite). The results show that the active polymer concentration can be substantially reduced by sorption onto clays: an impact which continues even after addition of further polymer to rejuvenate the fluids. The results also show that the current control parameters, Marsh funnel time and fluid density (an indicator of the total soil content), although useful are not sufficient to assess the active polymer concentration. If the active polymer concentration of used fluids is to be managed on site then specific testing must be undertaken.